Effects of Different Warm-up Protocols on Explosive Force in Volleyball Players - MERİÇLİ , Safa İlkin and TUTAR , Murat (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2024)
Volleyball is a sport that involves dynamic movements characterized by explosive force, including vertical jumping, forward jumping, and overhead ball throwing. The objective of this study was to investigate the impact of inhibition and mobilization techniques on explosive force outputs in female volleyball players. A total of 13 female volunteer athletes, aged between 18 and 27, from a volleyball team in Istanbul, were included in the study. The volunteers were assigned randomly and divided into two groups: the Foam Roller Group (FRG) with a sample size of 7, and the Activation Group (AG) with a sample size of 6. The selection of movements applied to the athletes was based on the muscle groups that are consistently utilized in both indoor and beach volleyball. The foam roller group applied soft cylindrical foam for 30 seconds to the gastrocnemius, biceps femoris, TFL (band), piriformis, and latissimus dorsi muscle groups. The activation group performs two sets of mini band abductions, which consist of four movements lasting 20 seconds each. Additionally, they do swiss ball prone cobra, swiss ball lying leg extensions, and mini band tibialis pull movements. Prior to training, all athletes underwent measurements for vertical jump (VJ), forward jump (FJ), and overhead ball throwing (BT). Once the FRG (Force-Recruitment Gain) and AG (Activation Gain) studies were finished for both groups, the measurements were recorded by repeating the Vertical Jump (VJ), Force Jump (FJ), and Ballistic Throw (BT) tests. This was done to assess how these tests influenced the explosive force outputs. The statistical analysis of the study using the SPSS 25.0 program did not find any notable difference (DS 0.086; IS 0.886; BF 0.174). However, in the FJ test, the FRG showed a statistically significant decrease in the pre-post-test measurement, with values of 2.12 ± 0.16 before the test and 1.99 ± 0.14 after the test. Consequently, while there is no detriment in engaging in short-term FR (flexibility and mobility) and activation exercises prior to sports performance, it can be inferred that these practices are carried out in order to mitigate the likelihood of injury.